Suzuki–Miyaura coupling of quinazolines containing an unprotected NH2 group: Synthesis and biological testing of quinazoline derivatives. Issue 12 (18th June 2017) - Pulipati, Yadagiri; Gurram, Venkateshwarlu; Laxmi, S. Vijaya; Satyanarayana, Yennam; Singh, Karan; Kumar, Vinod; Sharma, Somesh; Pottabathini, Narender; Iska, Vijaya Bhaskara Reddy
ABSTRACT: A robust approach to 4-amino quinazoline bi-aryl compounds was developed through Suzuki–Miyaura coupling reaction of quinazoline containing an unprotected NH2 group and arylboronic acids. Pd(dcpf)Cl2 was found to be an efficient catalyst for the reaction. All the compounds were evaluated for antimicrobial activity against gram-positive and gram-negative bacteria and fungi. One of the compounds, 3l, found to be more active against Candida albicans than the standard Miconazole. GRAPHICAL ABSTRACT: